Specifity of training 2 (1998)
This second issue of Volume 4 of Coaching Science Abstracts reviews 19 articles concerned with the benefits of specific training when compared to "general" or "cross-training." Interpretations are made with reference to athletes who train seriously. The implications for trained athletes are likely to be different to those for non-athletes who start a program of fitness development. Some items regarding the requirement for specific testing to obtain useful results for a particular activity are also included. Sub-topics are: Cross-training, Testing, Training Specificity.